Ambiguity in securitization markets - Anderson, Alyssa Gray (Journal of Banking & Finance, 2019)
During the financial crisis of 2008, origination and trading in asset-backed securities markets dropped dramatically. I present a model with ambiguity-averse investors to explain how such a market freeze could occur and to investigate how ambiguity affects origination and securitization decisions. The model shows how non-fundamental factors such as ambiguity can lead to market freezes and fire sales, as well as reductions in real economic activity. I consider the differing implications of a non-fundamental shock, such as ambiguity, and fundamental shocks, such as changes in risk or a deterioration of expected value. Market outcomes can change more abruptly under ambiguity than under either fundamental deterioration or risk alone. Additionally, ambiguity leads to different policy implications than fundamental shocks do.